HIGHLAND SPECIES AND TEMPERATURE REQUIREMENT FOR GERMINATION: A CASE FROM TWO ENDEMIC PAPUAN Pittosporum (PITTOSPORACEAE) SPECIES - Satyanti, Annisa; Kuswantoro, Farid; Susanto, Eko; Utomo, Trisno; Mahmudin, Mahmudin; Fijridiyanto, Izu Andry (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2015)
Climate change, including warming and drying, is currently the biggest challenge for plant regeneration. We conducted two experiments on how temperature affected the germination of Pittosporum pullifolium and P. spicessens, both endemic to Central Papua highlands. P. pullifolium habitat temperature at night could reach 8Â°C whereas P. spicessens habitat temperature ranged from 19Â°C early in the morning up to 26Â°C at midday. The first experiment was to understand the effect of chilling on P. pullifolium germination initiation. Our study showed that P. pullifolium was dependent on cold stratification for its germination. Without cold stratification the germination was absent even though the temperature range of sowing environment is at ca. 13â26Â°C (Cibodas Botanic Gardens). With a cold stratification at 6â8Â°C (constant) for more than a month, germination of P. pullifolium occurred, with better germination rate under a light. Subsequently we carried out extended cold stratification for a month and interestingly, the germination still occurred but now it is better under dark condition. For P. spicessens, the germination at its habitat temperature range (Wamena) and in the warmer environment (Bogor Botanic Gardens), both occurred at more than two weeks after sowing.